Antioxidants Benefits, Sources, Mechanisms of Action - Waisundara, Viduranga (IntechOpen, 2021)
Antioxidants are one of the most sought-after biological compounds of interest to both scientific and nonscientific communities. The term gained popularity with the advent of identifying these compounds as having the ability to maintain health and wellness by combating against pathways leading to non-communicable diseases. This book covers several aspects of antioxidants-mechanisms of action, assays of measuring potency, sources, and even methods of isolation and identification. While it may seem these aspects have been covered in depth in several publications before this, this book intends to be positioned as an update, especially since the area of antioxidant research is as dynamic as ever. There are several chapters that might be of interest to health buffs, specifically those who are quite keen on maintaining health and wellness.